ANTIMICROBIAL ACTIVITY OF SYZYGIUM CALOPHYLLIFOLIUM WALP. LEAF EXTRACT - Sumithra, N.; Kumar, Sevanan Rajesh (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: To evaluate the antimicrobial activity of methanol extract of Syzygium calophyllifolium Walp. leaf against the gram-negative bacteria, namely, Escherichia coli, Klebsiella pneumonia, Salmonella typhi, Proteus miriabilis and Pseudomonas aeruginosa, the gram-positive bacteria Bacillus cereus, Bacillus subtilis, Sarcina lutea, Staphylococcus aureus and Bacillus megaterium, three fungal species strains, commonly causing systemic infections in immune compromised patients such as Candida albicans, Aspergillus niger and Saccharomyces cerevisiae. Methods: The dried leaves were ground finely and extracted in methanol for 48 h at room temperature (26 °C-28 °C). This was then filtered using Whatman No.1 filter paper. The different concentration of (5 µl, 10 µl, 15 µl) methanol extract of leaves of S. calophyllifolium was investigated in vitro by an agar diffusion method and the MIC by macro-broth dilution method in the present study. The antibacterial antibiotics Ampicillin (10µ/ml), Ofloxin (1 mg/ml) and the antifungal antibiotics Nyastatin (20µg/ml), Tobramycin (10µ/ml) were used as positive controls. Results: The largest zone of inhibition was noted against E. coli (25±mm in diameter) and S. cerevisiae (25±mm in diameter) at the highest concentration (15 µl). B. cereus, K. pneumoniae, P. aeruginosa and E. coli showed the highest MIC (10±mg/ml) and MBC (20±mg/ml). Conclusion: The result revealed that the methanol extract of S. calophyllifolium leaf has a broad spectrum of antimicrobial activity. Keywords: Syzygium calophyllifolium, Eugenia calophyllifolia, Myrtaceae, Antimicrobial activity, Minimum inhibitory concentration